GE_GERICHTE C/15905/2015 vom 22. Mai 2017 - GE Cour de justice (2017)
BAIL À LOYER ; DÉFAUT DE LA CHOSE ; ISOLATION ; UTILISATION ; DOMMAGES-INTÉRÊTS ; MOTIVATION DE LA DEMANDE | CO.259.a; CPC.311.1; CO.259.d;